ASSOCIATION OF SMOKING AND PROSTATE CANCER : A 10 YEARS SYSTEMATIC REVIEW - Amal Ramadhani, Rizkia; Fithri Rofifa, Amira (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Prostate cancer (PCa) is the second most commonly diagnosed cancer and the fifth leading cause of cancer death among males, with an estimated 1.4 million new cases and 375 000 deaths worldwide in 2020, accounting for 7.3 and 3.8 of all cancers diagnosed, respectively. Various endogenous and exogenous risk factors for PCa have been discussed for decades. Several factors have been identified to be associated with an increased risk of PCa, for instance, family history, elevated hormone levels, black ethnicity, and high alcohol consumption. The aim: This study aims to show about association of smoking and prostate cancer. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 30 articles, whereas the results of our search on SagePub brought up 55 articles. The results of the search conducted for the last year of 2014 yielded a total 13 articles for PubMed and 23 articles for SagePub. The result from title screening, a total 10 articles for PubMed and 15 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Regarding smoking, burning tobacco and inhaling the smoke is considered a significant risk factor or direct cause of cancer, tumor lesions, and a well-known chemical carcinogen.